ผลการใช้รูปแบบรายงานการส่งเวรด้วยกระบวนการพยาบาลและการบริหารความเสี่ยงต่อความผิดพลาดในการสื่อสาร หอผู้ป่วยทารกแรกเกิดมีปัญหา โรงพยาบาลตำรวจ - สัจจะสกุลชัย, ศรีลาวัลย์; ชีวเกษมสุข, อารี (JOURNAL OF THE POLICE NURSES AND HEALTH SCIENCE, 2016)
การวิจัยครั้งนี้เป็นการวิจัยกึ่งทดลอง มีวัตถุประสงค์เพื่อ 1) ศึกษาความผิดพลาดในการสื่อสารจากการใช้รูปแบบรายงานการส่งเวรที่พัฒนาขึ้นด้วยกระบวนการพยาบาลและการบริหารความเสี่ยง หอผู้ป่วยทารกแรกเกิดมีปัญหา โรงพยาบาลตำรวจ และรูปแบบเดิม 2) เปรียบเทียบความผิดพลาดในการสื่อสารระหว่างการใช้รูปแบบรายงานการส่งเวรใหม่และรูปแบบเดิม 3) เปรียบเทียบความผิดพลาดในการสื่อสารระหว่างการใช้รูปแบบรายงานการส่งเวรใหม่และรูปแบบเดิม จำแนกตามเวรปฏิบัติงาน และ 4) เปรียบเทียบความผิดพลาดในการสื่อสารระหว่างเวรเช้า เวรบ่าย และเวรดึกจากการใช้รูปแบบรายงานการส่งเวรใหม่และรูปแบบเดิม ตัวอย่างเป็นพยาบาลที่ปฏิบัติงานในหอผู้ป่วยทารกแรกเกิดมีปัญหา ได้จากการคัดเลือกแบบเจาะจง จำนวน 10 คน เครื่องมือที่ใช้ในการทดลอง ได้แก่ 1) รูปแบบรายงานการส่งเวรด้วยกระบวนการพยาบาลและการบริหารความเสี่ยง 2) โครงการอบรมเชิงปฏิบัติการ และ 3) แบบรายงานความผิดพลาดในการสื่อสาร เครื่องมือวิจัยผ่านการตรวจสอบความตรงตามเนื้อหาจากผู้เชี่ยวชาญ 3 ท่าน และหาความเที่ยงของเครื่องมือส่วนที่ 3 โดยการคำนวณหาดัชนีความสอดคล้องตามสูตรของสก็อทท์ได้เท่ากับ .95 วิเคราะห์ข้อมูลโดยการหาความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน สถิติที และสถิติการวิเคราะห์ความแปรปรวนแบบทางเดียว ผลการวิจัยพบว่า 1) ความผิดพลาดในการสื่อสารจากการใช้รูปแบบรายงานการส่งเวรด้วยกระบวนการพยาบาลและการบริหารความเสี่ยงและรูปแบบเดิมเท่ากับ 1.46 ครั้ง และ 8.76 ครั้ง ตามลำดับ 2) ความผิดพลาดในการสื่อสารจากการใช้รูปแบบรายงานการส่งเวรใหม่น้อยกว่ารูปแบบเดิมอย่างมีนัยสำคัญทางสถิติที่ระดับ .001 3) ความผิดพลาดในการสื่อสารจากการใช้รูปแบบรายงานการส่งเวรใหม่ทั้งเวรเช้า เวรบ่าย และเวรดึกน้อยกว่ารูปแบบเดิมอย่างมีนัยสำคัญทางสถิติที่ระดับ .001 และ 4) ความผิดพลาดในการสื่อสารจากการใช้รูปแบบรายงานการส่งเวรใหม่และรูปแบบเดิมระหว่างเวรเช้า เวรบ่าย และเวรดึก ไม่แตกต่างกันอย่างมีนัยสำคัญทางสถิติ EFFECTS OF UTILIZING A CHANGE OF SHIFT MODEL WITH THE NURSING PROCESS AND RISK MANAGEMENT ON COMMUNICATION ERRORS AT AN INTERMEDIATE CARE UNIT, POLICE GENERAL HOSPITAL Abstract The purposes of this quasi-experimental study were: 1) to study communication errors of using a change of shift report model which was developed based on the nursing process and risk management and a previous model at an intermediate care unit of Police General Hospital, 2) to compare communication errors between using the new model and the previous one, 3) to compare communication errors between two models which was classified into working shifts, and 4) to compare communication errors among the morning shift, the evening shift, and the night shift in using two models. The samples included 10 professional nurses who worked at the intermediate care unit in the Police General Hospital, and they were chosen by purposive sampling. The study tools consisted of: 1) the change of shift report model which was developed based on the nursing process and risk management, 2) a training program, and 3) an appraisal checklist of communication errors. The validity of the tools was verified by three experts. The third section which was done for reliability by inter-rater reliability of Scott analysis was .95. Data were analyzed by descriptive statistics (percentage, mean, and standard deviation), paired t-test, and one-way analysis of variance. The findings were as follows: 1) The communication errors in using the new change of shift report model based on the nursing process and risk management and the previous one were 1.46 and 8.76 times respectively. 2) The communication errors in using the new model were significantly less than the previous one (p < .001). 3) The communication errors in using the new model during the morning shift, the evening shift, and the night shift was all significantly less than the previous one (p < .001). 4) Finally, the communication errors in using the new model and the previous one during the morning shift, the evening shift, and the night shift were not significantly different.